Developing a PSADS-Based “Find Objects” Learning Media to Enhance Critical Thinking Skills of Third-Grade Elementary Students in Mathematics - Antonius Ferrian Dwi Prasetyo; Helti Lygia Mampouw; Wahyu Hari Kristiyanto (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to develop and evaluate a PSADS-based “Find Objects” learning media that is valid, practical, and effective in enhancing the critical thinking skills of third-grade elementary school students in mathematics. Methodology: The study employed a Research and Development approach using the ADDIE model. Data were collected through expert validation sheets, teacher and student questionnaires, classroom observations, and critical thinking tests. The test instruments were developed based on the FRISCO critical thinking indicators. Data analysis techniques included descriptive statistics, Kolmogorov–Smirnov normality tests, paired sample t-tests, and qualitative analysis using MAXQDA 2020 software. Main Findings: The PSADS-based “Find Objects” learning media was categorized as feasible to very feasible by material, instructional design, and practitioner experts. Teacher and student responses indicated a high level of practicality. Statistical analysis revealed a significant improvement in students’ critical thinking skills, with a mean score increase of 14.27 points. The paired sample t-test confirmed a significant difference between pre-test and post-test scores (p < 0.05). Novelty/Originality of this study: This study fills a research gap in elementary mathematics education, where prior studies have largely emphasized instructional models or learning outcomes without integrating concrete visual media to systematically train critical thinking processes. The novelty of this study lies in the integration of the PSADS learning stages with a “Find Objects” card-based media that engages students in structured object-search, analysis, discussion, and reflection activities, thereby emphasizing critical thinking development rather than learning outcomes alone.